Study of clinical profile of megaloblastic anemia: An experience of six year at Kathmandu University Hospital, Dhulikhel - Pokharel, BR; Pant, P; Gurung, R; Koju, R; Bedi, TRS; Makaju, R; Sanjel, S (Journal of College of Medical Sciences-Nepal, 2012)
Megaloblastic anemia is not uncommon, however varied of presentation makes difficult to come to conclusion. It’s more difficult when resources are limited. In this back ground clinical features of megaloblastic anemia are very important for diagnosis and treatment. It is a retrospective analysis of data from December 2003 to September 2009. During the period, bone marrow aspiration was done for analysis of cause and type of anemia.A total of 14 cases bone marrow findings was consistent with megaloblastic anemia. These reports were taken into consideration after pathologist impression. Serum Vitamin B12 and RBC folate were not done in view of limited resources and financial constrain. In the analysis 14 (11.96%) bone marrow findings were consistent with megaloblastic anemia. Regarding clinical presentation; pallor was 13 (92.85%) followed by glossitis 5 (35.71%) and Jaundice 5 (35.71%), paresthesia 3 (21.42%), and pigmentation, ataxia, confusion each case (7.14 %). Mostly the patients were between the 21- 40 years of age. Megloblastic anemia is common clinical problem with pallor and glossitis as major presentation. However some had neurological features. This disease can be diagnosed and treated on the basis of bone marrow aspiration when resources are limited. Journal of College of Medical Sciences-Nepal, 2011, Vol-7, No-2, 41-44 DOI: http://dx.doi.org/10.3126/jcmsn.v7i2.6679